P13 Gender differences during jump landing/cutting in lower extremity kinetic and energetic patterns in chronic ankle instability. (17th September 2017) - Evans, A; Son, SJ; Kim, H; Seeley, MK; Hopkins, JT
Abstract : Study Design: Single cohort, descriptive. Objectives: To identify how movement kinetics and energetics alterations in chronic ankle instability (CAI) differ between genders. Background: The chronic nature of ankle instability has been reported across genders, however, it is unclear how/if gender affects lower extremity landing/cutting biomechanics in CAI. Methods and Measures: 100 CAI (M=54, F=46; 22±2 years, 174±9 cm, 72±14 kg, 82%±9% FAAM-ADL, 62%±13% FAAM-Sport, 3.6±1.2 MAII, 4.3±3 ankle sprains) and 100 matched controls (M=54, F=46; 22±3 years, 172±13 cm, 72±18 kg, 100% FAAM-ADL, 100% FAAM-Sport, 0 MAII, 0 ankle sprain) performed five trials of jump landing/cutting (maximum vertical forward jump, landing on the test leg only, and immediate 90° side-cutting). A functional data analysis (α=0.05) was used to detect a group ×gender interaction for joint moment (Nm/kg) and power (W/kg) across the entire ground contact time (0%=initial contact, 50%=peak flexion, 100%=toe off) during jump landing/cutting. If 95% confidence intervals did not cross the zero, significant differences existed. Results: No maximum vertical jump height differences were observed within genders, between groups (p>0.05). Several group ×gender interactions were observed: males in the CAI group had reduced plantarflexion moment (46%–84% of stance), increased knee extension moment (0%–17% of stance), reduced hip extension moment (0%–6% of stance) and increased hip extension moment (9%–15% of stance). Males in the CAI group also showed reduced eccentric ankle power (12%–16% of stance), reduced concentric ankle power (77%–90% of stance), and increased knee (3%–16% of stance) and hip eccentric power (4%–12% of stance). Conclusions: Both males and females in the CAI group demonstrated altered kinetic and energetic patterns relative to the control group, and more between-group alterations were observed in males relative to females. Males with CAI appeared to use an interlimb reweighting strategy from distal to proximal joints, which may be due to greater sensorimotor dysfunction.